Arbuscular Mycorrhizal Fungi-Assisted Phytoremediation: A Promising Strategy for Cadmium-Contaminated Soils - Shaopeng Zhao; Lei Yan; Muhammad Kamran; Shanshan Liu; Muhammad Riaz (Plants)
Arbuscular mycorrhizal fungi (AMF) have been shown to play a major role in regulating the accumulation, transport, and toxicity of cadmium (Cd) in plant tissues. This review aims to highlight the current understanding of the mechanisms by which AMF alleviate Cd toxicity in plants. Cd accumulation in agricultural soils has become an increasing global concern due to industrial activities and the use of phosphatic fertilizers. Cd toxicity disrupts various physiological processes in plants, adversely affecting growth, photosynthesis, oxidative stress responses, and secondary metabolism. AMF alleviate Cd stress in plants through multiple mechanisms, including reduced Cd transport into plant roots, improved plant nutritional status, modulation of organic acid and protein exudation, enhanced antioxidant capacity, and maintenance of ion homeostasis. AMF colonization also influences Cd speciation, bioavailability, and compartmentalization within plant tissues. The expression of metal transporter genes, as well as the synthesis of phytochelatins and metallothioneins, are modulated by AMF during Cd stress. However, the efficacy of AMF in mitigating Cd toxicity depends on several factors, such as soil properties, plant species, AMF taxa, and experimental duration. Further knowledge of the intricate plant–AMF–Cd interactions is crucial for optimizing AMF-assisted phytoremediation strategies and developing Cd-tolerant and high-yielding crop varieties for cultivation in contaminated soils.